Variable speed control for 2Ph-HSM in RGS: a comparative simulation study - Salam Waley Shneen; Mohammed Qasim Sulttan; Manal Hadi Jaber (Institute of Advanced Engineering and Science, 2020)
There are many applications of two-phase hybrid stepping motor (2Ph-HSM) system. The robotic grinding system (RGS) one of these applications. In this work, under the title variable speed control. The aim is Simulink the 2Ph-HSM in RGS with a proportional-integral controller (PIC) and optimization unit such as Genetic Algorithm (GA) which tuning PIC as (GA_PIC) to improve the RGS action by improving the parameters of PIC. Also comparing the act of PIC and GA_PIC to see which state is the best. The simulation results of this work show the GA_PIC is the best that comparative with PIC.